Within - tree variations in decay resistance basic density and fibre length in acacia mangium willd. wood - Rita, Andreas. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Both heartwood and sapwood ofAcacia mangium sampled at 25% height (about 147.5 em high) and 75% height (about 442.5 em high) were subjected to attack by white rot (Pycnoporus coccineus) and soft rot (Chaetomium g/obosum) fungi. Heartwood showed lower percentage of mass losses relative to sapwood. Sapwood has low decay resistance, with overall mean percentage of mass losses (8.5%) due to both white rot and soft rot. The highest mean percentage of mass loss (17.0%) occurred at 75% height of tree stem in sapwood and was due to white rot. The lowest mean percentage of mass loss recorded was 0.8%, which occurred at 25% and 75% height of tree stem in inner heartwood, middle heartwood and outer heartwood and was due to soft rot infection. The mean basic density in Acacia mangium has increase constantly from inner heartwood at 4.42 em from pith (0.463 g em-3) to middle heartwood at 6.62 em from pith (0.531 g cm-3) and outer heartwood at 8.68 em from pith (0.600 g cm-3). However the mean basic density has decreased in sapwood at 10.64 em from pith (0.548 g cm-3). This pattern of basic density was consistent for both 25% and 75% height of the tree stem. The mean basic density of bottom tree is higher (0.577 g cm-3) than the upper height (0.493 g cm-3). There was little variation for fibre length in axial and radial variation with overall mean fibre length (1.05 mm) at 25% height and 1.06 mm at 75% height. There is significant correlation between percentage mass losses and percentage basic density loss due to white rot. There is no relationship between fibre length and basic density, also no relationship between basic density and mas loss due to each fungus. There is also no correlation between basic density and mass loss due to each fungus in Acacia mangium.